Cornus × elwinortonii and Cornus × rutgersensis (Cornaceae), new names for two artificially produced hybrids of big-bracted dogwoods - Robert Mattera; Thomas Molnar; Lena Struwe (PhytoKeys, 2017)
Big-bracted dogwoods (Cornus sp.) are well-known plants in North America and eastern Asia where they occur as wild, generally spring-flowering understory trees. They are also popular ornamental landscape plants, and many economically important cultivars are propagated and sold across North America, Europe, and Asia. Starting in the late 1960s, Elwin Orton of Rutgers University in New Jersey (USA) utilized three geographically disjunct species of dogwoods, C. florida (eastern North America), C. nuttallii (western North America), and C. kousa (East Asia), in an extensive interspecific hybridization program. He was successful in developing the first-ever interspecific F1 hybrids of these species, several of which have become staple items in the ornamental nursery trade due to their enhanced ornamental qualities and resistance to diseases. The original F1 plants are still alive at Rutgers University. While they have been available for decades in horticultural commerce, the interspecific hybrid crosses were never formally described and their scientific hybrid names were never published. For the C. kousa × C. florida hybrids, the name Cornus ‘rutgersensis’ has been used on occasion in the horticultural trade, but without proper citation and description. Here, it is formally named Cornus × rutgersensis Mattera, T. Molnar, & Struwe, hybr. nov. For the C. kousa × C. nuttallii hybrids, no previous name has been used, and it is hereby named Cornus × elwinortonii Mattera, T. Molnar, & Struwe, hybr. nov. The need for providing scientific names for commonly used horticultural hybrids is discussed. Holotype material for both hybrid names was collected from the original F1 hybrids for full documentation, typification, and description. The comparative intermediate development of leaves, inflorescence structures, and fruit types of the hybrids and their parents is discussed and illustrated. Etymology, phenology, and cultivation aspects of these hybrids and their cultivars including backcrosses to C. kousa are also presented.